On design of novel bionic bamboo tubes for multiple compression load cases. (15th March 2022) - Liang, Hongyu; Hao, Wenqian; Sun, Hao; Pu, Yongfeng; Zhao, Ying; Ma, Fangwu
Highlights: Three kinds of bionic bamboo tubes (BBT) are introduced in this paper. Explore the crashworthiness of different structural configurations under multi-angle compression loads. Explore the effect of the cross-section feature and the gradient distribution feature on crashworthiness. Reveal the superiority of BBT structure in energy absorption capacity for multiple load cases. Abstract: A bamboo bio-inspired method is developed to enhance the energy absorption capacity of thin-walled tube for multiple load cases. Based on the simplified double-ring cross-section feature and the gradient distribution feature of bamboo knots, three kinds of bionic bamboo tubes (BBT-I, BBT-II, BBT-III) are introduced in this paper. A comparative study on the BBT-I, BBT-II, BBT-III, and hollow circle tube is performed to explore the crashworthiness of different structural configurations under multi-angle compression loads based on the validated simulation model. The corresponding prediction formulas of mechanical properties are deduced. The BBT structures show great potential in enhancing the specific energy absorption compared with the hollow tube, and the BBT-II and BBT-III structures show remarkable energy absorption effects under large-angle cases. A detailed parametric research is carried out to explore the effect of the cross-section feature and the gradient distribution feature on the specific energy absorption, peak crushing force, and collapse deformation patterns of BBTs. Furthermore, a crashworthiness comparison of BBT and typical multi-cell structures is carried out to reveal the superiority of BBT structure in energy absorption capacity for multiple load cases. This study provides valuable suggestions and guidelines for developing the bio-inspired multi-cell structure under multiple loading cases. Graphical abstract: Image, graphical abstract